MAKNA TATO BAGI KAUM PEREMPUAN DI KOTA PEKANBARU - Nur Indra Sari Pane; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Tattoo culture in Indonesia is known as one of the forms of art body painting, tattoo creating a new phenomenon in the society. In this case how society's view of a woman who has a tattoo on his body and then how to view the response of the family when the find out his son has a tattoo on his body. Women who decide to make a tattoo on his body certainly understand once will get a skewed view by the social environment. This kind of thing makes those who initially do not have a tattoo until his tattoos certainly should be with a reason or a strong meaning. The studied phenomenon this time is located in the Pekanbaru city, there are the characteristics of the informants according to the subject being studied. Research data collection is done by interview, observation and documentation. The interview conducted is structured interviews where the researchers first prepare the guidelines for the interview. The researcher aims to know how the meaning of tattoos for women in the Pekanbaru city and to determine the factors that influence women's use of the tattoo in the city of Pekanbaru. The results of this study showed that the reason women use permanent tattoo in the Pekanbaru city influenced by lifestyle as well as background work in which they live. Keywords: Tattoo, Women.